Robustness Report on "Coercive Contract Enforcement: Law and the Labor Market in Nineteenth Century Industrial Britain", by Suresh Naidu and Noam Yuchtman (2013) - Douglas Campbell; Abel Brodeur; Magnus Johannesson; Joseph Kopecky; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
Naidu and Yuchtman (2013) find that labor demand shocks in 19th-century Britain had an impact on master and servant prosecutions, as breaking an employee contract was a criminal offense until 1875. We first reproduce all regression tables in Naidu and Yuchtman (2013) and then test for robustness by using a triple difference where we compare the impact of labor demand shocks on master and servant prosecutions relative to other prosecutions, changing the functional form of key variables, including region*year interactive fixed effects, and conducting influential analysis. We find that the results are sensitive to the triple difference specification and to region*year FEs, and otherwise robust. Overall, we find the results are robust in 50% of the checks we ran, and the t/z scores were on average 74% as large as the original study.
Keywords: J31; J41; K12; K31; N33; N43; 330; Labor Law; Contract Law; Labor Contracts; Labor Market Institutions; Economic History